Narrative Transculturation in the Stories of Carmen Lyra - García-Rey, María del Rocío (2016)
This work focuses on the children's stories of Carmen Lyra, the Costa Rican author of Cuentos de mi tía Panchita (Stories about my Aunt Panchita, 1922). Our approach is an extrapolation from several of the points made by Angel Rama's  landmark work Narrative Transculturation in Latin America. While we are aware of the fact that Rama's work does not specifically address children's literature, it does present us with valuable elements to help explain the cultural game in which the re-writing and "translation" of Lyra's stories are immersed.